Analisis Data Chat Whatsapp Group Dengan Python - , Isnardi; , Darwati (GLOBAL SCIENTS PUBLISHER, 2025)
The study uses Python-based methods to understand digital communication patterns by analyzing conversation data from three WhatsApp groups. Message frequency analysis, communication time patterns, sentiment analysis, and identification of dominant topics are all quantitative and qualitative methods used to analyze the extracted data. The results showed that communication patterns varied depending on the type of group. Professional groups have a more formal and organized communication pattern, while social groups have a more relaxed and active communication pattern throughout the day. These results give us an idea of the dynamics of digital interactions on instant messaging platforms. They also pave the way for further analysis in the technological and social domains. The study is expected to help academics and practitioners understand how people communicate in WhatsApp groups.